2019
DOI: 10.1152/ajpgi.00056.2019
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics analysis of maternal-placental-fetal metabolism in pregnant swine reveals links in fetal bile acid homeostasis and sulfation capacity

Abstract: Cholestasis of pregnancy endangers fetal and neonatal survival, yet systematic knowledge of the cause and effect of disrupted bile acid (BA) homeostasis in pregnancy is limited. Here we show that gestation stage-associated BA dysregulation in swine correlated with fetal death resulting from compromised capacity for BA secretion and increased alternative systemic efflux. The balance of BA input and output in the developing uterus suggested little uptake and metabolism of maternal BA by the placenta-fetus unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Consistent with results in pregnant women [15], maternal BA metabolism in pregnant swine was dysregulated with the advance of pregnancy [8]. In addition, our recent study also indicated the impairment of placental BA transport function as pregnancy advanced, which further affected the BA homeostasis of fetuses [8]. However, the genetic and molecular basis for placenta to perform preprogrammed function, particularly BA metabolism, is largely undetermined as pregnancy advances.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Consistent with results in pregnant women [15], maternal BA metabolism in pregnant swine was dysregulated with the advance of pregnancy [8]. In addition, our recent study also indicated the impairment of placental BA transport function as pregnancy advanced, which further affected the BA homeostasis of fetuses [8]. However, the genetic and molecular basis for placenta to perform preprogrammed function, particularly BA metabolism, is largely undetermined as pregnancy advances.…”
Section: Introductionsupporting
confidence: 78%
“…Studies in ICP patients and maternal cholestasis model during pregnancy have shown the impaired placental function, including the reduced fetal BA transport from fetuses to mother [18] and placental oxidative stress and apoptosis (19) [19]. Consistent with results in pregnant women [15], maternal BA metabolism in pregnant swine was dysregulated with the advance of pregnancy [8]. In addition, our recent study also indicated the impairment of placental BA transport function as pregnancy advanced, which further affected the BA homeostasis of fetuses [8].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…It was found that sulfation played a pivotal role in maintaining BA homeostasis in the fetus. Furthermore, fetal mortality showed an exponential increase in relation to the total BA increase from week 60 to week 90 [109]. A controversial condition related to ICP that is asymptomatic and difficult to distinguish from ICP is asymptomatic hypercholanemia of pregnancy (AHP).…”
Section: Cholestasismentioning
confidence: 99%